Investigating The Competence Of Spiritual Care Among Nurses Working In Teaching Hospitals Affiliated With Shahid Sadoughi University Of Medical Sciences In Yazd, 2023 - Roohollah Askari; Hassan Jafari; Arefeh Dehghani Tafti; Neda Futuhi Tafti (بیمارستان, 2024)
Background and purpose: Nurses, as the closest healthcare providers to patients, hold significant popularity and trust. Strengthening their competence in spiritual care is critical in ensuring holistic healthcare delivery. This study aimed to evaluate the spiritual care competence of nurses working in selected teaching hospitals of Shahid Sadoughi University of Medical Sciences in Yazd in 2023. Methods: This cross-sectional study was conducted on 262 nurses employed in three selected teaching hospitals (Shahid Sadoughi, Shahid Rahnamoun, and Afshar hospitals). Data were collected using the Standard Spiritual Care Competence Questionnaire (SCCS) and analyzed through ANOVA, Mann-Whitney, Kruskal-Wallis tests, and Spearman's correlation coefficient using SPSS version 21 software. Results: The overall mean score and standard deviation of spiritual care competence among nurses were 83.9±18.2, indicating an optimal level of competence. Among the dimensions of spiritual care competence, the "personal support and consultation with the patient" dimension scored the highest (18.8±5.2), while the "communication" dimension scored the lowest (7.3±1.6). The highest overall competence score was observed at Shahid Rahnamoun Hospital (88.5±17.7) Conclusion: While the overall competence in spiritual care among the nurses studied was favorable, the low score in the communication dimension highlights the need for workshops focused on effective nurse-patient communication. Developing these skills can significantly enhance nurses' roles in improving patient health outcomes.